GPR/GPS/IMU system as buried objects locator. (January 2018) - Ferrara, Vincenzo; Pietrelli, Andrea; Chicarella, Simone; Pajewski, Lara
Highlights: Buried objects locator system based on GPR. Integration of GPS and IMU functionalities dedicated to GPR use. Low cost electronic board design as suitable solution with GPS and IMU unit. Abstract: In the last years, Ground Penetrating Radar (GPR) technology has been extensively used in several different fields, including archaeology and cultural-heritage diagnostics. The integration of GPR with other positioning devices, such as a Global Positioning System (GPS) and an Inertial Measurement Unit (IMU), can significantly improve the accuracy of buried-object location, by means of an efficient control of GPR route and attitude. This article aims at investigating solutions for an accurate location of buried objects when a GPR is pulled by a terrestrial vehicle or carried by an aerial platform. In particular, a low-cost system is presented, which integrates functionalities of GPS and IMU specifically dedicated to GPR use. The device has been designed, realized and finally its performance was tested in the laboratory.